Mortality burden of ambient fine particulate air pollution in six Chinese cities: Results from the Pearl River Delta study. (November 2016) - Lin, Hualiang; Liu, Tao; Xiao, Jianpeng; Zeng, Weilin; Li, Xing; Guo, Lingchuan; Zhang, Yonghui; Xu, Yanjun; Tao, Jun; Xian, Hong; Syberg, Kevin M.; Qian, Zhengmin (Min); et al.
Abstract: Background: Epidemiological studies have reported significant association between ambient fine particulate matter air pollution (PM2.5 ) and mortality, however, few studies have investigated the relationship of mortality with PM2.5 and associated mortality burden in China, especially in a multicity setting. Methods: We investigated the PM2.5 -mortality association in six cities of the Pearl River Delta region from 2013 to 2015. We used generalized additive Poisson models incorporating penalized smoothing splines to control for temporal trend, temperature, and relative humidity. We applied meta-analyses using random-effects models to pool the effect estimates in the six cities. We also examined these associations in stratified analyses by sex, age group, education level and location of death. We further estimated the mortality burden (attributable fraction and attributable mortality) due to ambient PM2.5 exposures. Results: During the study period, a total of 316, 305 deaths were recorded in the study area. The analysis revealed a significant association between PM2.5 and mortality. Specifically, a 10 μg/m 3 increase in 4-day averaged (lag03 ) PM2.5 concentration corresponded to a 1.76% (95% confidence interval (CI): 1.47%, 2.06%) increase in total mortality, 2.19% (95% CI: 1.80%, 2.59%) in cardiovascular mortality, and 1.68% (95% CI: 1.00%, 2.37%) in respiratory mortality. The results were generally robust to model specifications and adjustment of gaseous air pollutants. We estimated that 0.56% (95% CI: 0.47%, 0.66%) and 3.79% (95% CI: 3.14%, 4.45%) of all-cause mortalities were attributable to PM2.5 using China's and WHO's air quality standards as the reference, corresponding to 1661 (95% CI: 1379, 1946) and 11, 176 (95% CI: 9261, 13, 120) attributable premature mortalities, respectively. Conclusion: This analysis adds to the growing body of evidence linking PM2.5 with daily mortality, and mortality burdens, particularly in one Chinese region with high levels of air pollution. Highlights: We observed a significant association between PM2.5 and mortality. A 10 μg/m 3 increase in PM2.5 corresponded to 1.76% all cause mortality increase. About 3.79% of all-cause mortalities were attributable to PM2.5 .